What Would Make Morocco an Emerging Economy? - Naciri, Ahmed (Archives of Business Research, 2020)
Morocco is steadily progressing toward development and may well join the ranks of rich countries as early as in 2022. We perform least squares regressions on a sample of 12 components of economic freedom, for a total of 375 observations over 25 years (1995-2019). We also consider Morocco’s Gross Domestic Product (GDP) in USD billion, Morocco’s GDP growth as a percentage of change (pcGDP)and Morocco’s per capita GDP based on purchasing power parity (PPP) in USD for the last 25 years. The empirical evidence shows that during this period, Morocco achieved an enviable level of performance by increasing its GDP by 455%, despite the strong demographic pressures exerted by 35% population growth.[1] However, the country’s performance in relation to some components of its economic freedom was so weak that it may end up jeopardizing this economic development momentum, as expressed by the behaviour of its pcGDP and the increase of this value over time. Morocco must introduce some fundamental changes in its economic freedom policies if it wishes to continue to progress. Fortunately, the country appears to have the determination to do so. [1]According to the IMF, Morocco’s population grew from 26.7995 million in 1995 to 36.47 million in 2019, an increase of 36%.